Robot-Assisted Partial Nephrectomy Mid-Term Oncologic Outcomes: A Systematic Review - Vartolomei, Mihai Dorin; Remzi, Mesut; Fajkovic, Harun; Shariat, Shahrokh F (Journal of clinical medicine, 2022)
Robot-assisted partial nephrectomy (RAPN) is used more and more in present days as a therapy option for surgical treatment of cT1 renal masses. Current guidelines equally recommend open (OPN), laparoscopic (LPN), or robotic partial nephrectomy (PN). The aim of this review was to analyze the most representative RAPN series in terms of reported oncological outcomes. (2) Methods: A systematic search of Webofscience, PUBMED, Clinicaltrials.gov was performed on 1 August 2022. Studies were considered eligible if they: included patients with renal cell carcinoma (RCC) stage T1, were prospective, used randomized clinical trials (RCT) or retrospective studies, had patients undergo RAPN with a minimum follow-up of 48 months. (3) Results: Reported positive surgical margin rates were from 0 to 10.5%. Local recurrence occurred in up to 3.6% of patients. Distant metastases were reported in up to 6.4% of patients. 5-year cancer free survival (CFS) estimates rates ranged from 86.4% to 98.4%. 5-year cancer specific survival (CSS) estimates rates ranged from 90.1% to 100%, and 5-year overall survival (OS) estimates rated ranged from 82.6% to 97.9%. (4) Conclusions: Data coming from retrospective and prospective series shows very good oncologic outcomes after RAPN. Up to now, 10-year survival outcomes were not reported. Taken together, RAPN deliver similar oncologic performance to OPN and LPN.
Keywords: partial nephrectomy; nephron-sparing surgery; robot-assisted; overall survival; metastasis; renal cancer; cancer-specific survival